Combined effects of heavy metal toxicity and salinity on wheat: Challenges and mitigation strategies - George, Deodate Jose; Pandey, Vanita; Rinki; H M, Mamrutha; Firoda, Mahendra; Rani, Preety; Wadhwa, Zeenat; Kumar, Yogesh; Singh, Mukesh Kumar; K, Gopalareddy; Girimalla, Vanishree (Indian Farming, 2025)
Wheat (Triticum aestivum), a staple crop nourish nearly 40% of the global population, is increasingly threatened by soil salinity and heavy metal contamination. These stresses, often occurring together, impair photosynthesis, disrupt nutrient uptake, and enhance oxidative damage, leading to reduced yield and grain quality. Heavy metals such as lead (Pb), cadmium (Cd), arsenic (As), and chromium (Cr) accumulate in plant tissues and pose serious food safety concerns. Salinity further aggravates the problem by inducing osmotic stress. This article summarizes the combined effects of salinity and heavy metal toxicity on wheat growth and phenology, and outlines detoxification mechanisms including sequestration, chelation, and antioxidant defense. Sustainable mitigation strategies, such as plant growth-promoting rhizobacteria (PGPR), phytoremediation, bioremediation, organic amendments, and salt/metal-tolerant varieties offer effective solutions. Integrating agronomic, biological, and molecular approaches is essential to sustain wheat productivity and ensure food security under these dual stresses.